Faktor Yang Mempengaruhi Struktur Modal Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Brigitte Angeline, Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this research is to analyze dividend, asset structure, corporate size, liquidity, trading growth, and corporate risk which affecting capital structure at manufacturing company listed in Indonesia Stock Exchange for the period 2015-2018. The research samples uses secondary data and using purpose sampling method so there is 180 data manufacturing companies are used in this study. Data processing techniques using SPSS 26. The results of F test shows dividend, asset structure, corporate size, liquidity, trading growth, and corporate risk has significant effect on capital structure. t test results shows that dividend, asset structure, corporate size, and liquidity has no significant effect on capital structure while corporate risk has a significant positive effect on capital structure and trading growth has a significant negative effect on capital structure.